The physical modeling legacy of Frei Otto. Issue 1 (March 2016) - Goldsmith, Nicholas
Physical modeling as a developmental iterative process was one of the primary legacies of Frei Otto in his quest for a formfinding design tool. Exploring first hand knowledge of his sketching, and then incremental physical modeling techniques, we look at Otto's global approach to problem solving through design. Numerous actual projects of Otto including the BP Dyce Tent in Scotland and the KOCOMMAS project in Saudi Arabia are described in terms of this process as a better way of understanding his approach. A comparison of the formfinding and shape making approach to design is examined. In contrast to Otto's physical modeling, digital modeling & parametric approaches are also investigated to show Otto`s influence and evolution in contemporary modeling of complex surface geometries, but also to point out the seismic change that is presently occurring in the architectural profession.